Ability of children aged 5-16 years to perform scat3 and child-scat3 testing in the emergency department. Issue 11 (25th May 2017) - Babl, Franz E; Dionisio, Diana V; Davenport, Lucy; Baylis, Amy; Hearps, Stephen; Bressan, Silvia; Anderson, Vicki; Oakley, Ed; Davis, Gavin A
Abstract : Objective: To evaluate children's ability to perform the child-SCAT3 and SCAT3 Sports Concussion Assessment Tool. Design: Prospective observational study. Setting: Tertiary children's hospital emergency department. Participants: 264 children presenting to ED with concussion (CONC, n=90) and two control groups (i) upper limb injury (ULI, n=90) and (ii) well children (WELL, n=84) with equal sized subgroups in three age bands of 5–8, 9–12, and 13–16 years. Assessment and outcome: Ability to complete SCAT subtests administered by trained research assistants, stratified by age band and participant group. Child-SCAT3 was used for 5–12 years, SCAT3 for 13–16 years. Results: Inability to complete at least one sub-test of child-SCAT3 occurred in 29 (32.2%) of the 5-8 year age band and 5 (5.5%) in the 9–12 year age band. The 5 and 6 year olds had the lowest completion rates. In the 13–16 year age band 11 (13.3%) participants were unable to complete at least one sub-test of SCAT3. The most frequent reasons for inability to complete any sub-test (n=116) were 'did not understand' (n=45), and 'refusal to continue' (n=26). Fewer were due to 'feeling too unwell to continue' (n=13).The subtests with the highest rates of inability to complete were child-SCAT3 and SCAT symptoms scale (n=17), BESS (n=9), coordination (n=9), digits backwards (n=8) and concentration (n=8). Conclusions: Child-SCAT3 should be applied with caution in young children due to an inability to understand certain test items and may need to be modified. SCAT3 can be reliably applied in teenagers 13–16 years of age. Competing interests: GAD is an honorary member of the Australian Football League Concussion Working Group, and has attended meetings organised by sporting organisations including the National Football League (USA), National Rugby League (Australia) and FIFA (Switzerland); however has not received any payment, research funding, or other monies from these groups other than for travel costs. GAD is a member of the International Concussion in Sport group that developed the SCAT3 and ChildSCAT3.